Lessons for creating a culture of character and peace in your classroom : a playbook for teachers - DeRoche, Edward F.; Moloney, CJ; McGinty, Patricia J. (Peace education., 2021)
The intent of this playbook is to enable PK-12 teachers, teachers-in-training, counselors, and coaches to use character and peace education lessons to enrich their curriculum and help students expand their knowledge and understanding of themes and content in each of the book's chapters.The lesson plans will help students discover, learn, reflect on, and make connections between and among each of the chapters in the book, such as Character Development, Peace Awareness, Special Skills, Self-discipline, Respect, Responsibility, Relationships, and Conflict Resolution.This playbook is designed in such a way that you may take any one of the lessons and implement it at any time you find a teachable moment or want to focus on a particular topic or theme. The lessons have been designed to help you and your students "reflect" upon and make "connections" between the content and activities of each lesson.At the end of each chapter is a stop-sign symbol suggesting one "read/reflect/respond." The playbook is rich in references, research, and resources.